A Teacher’s Experiences on the Use of E-Portfolio as Students’ Portfolio Assessment in Teaching Speaking : A Narrative Inquiry - Putri Lasminiar (Universitas Pahlawan Tuanku Tambusai, 2022)
This article discusses the use of the e-portfolio as students’ portfolio assessment done by an English teacher in teaching speaking at junior high school level. The narrative inquiry was chosen as the research design to reveal the story of the English teacher’s experiences in using e-portfolio. The research data was obtained from the teacher through an interview and then it was analyzed via narrative analysis.The findings of the study indicated that ; 1) the reasons why the teacher used e-portfolio were related to the students’ attention and the shifting of assessment method from traditional method to modern method .Furthermore, it also compiled the students’ speaking assignments along with its assessment neatly. Meanwhile, the problems that the teacher faced in using the e-portfolio were related to unstable internet connection and the difference of students’ ability in running it. The results suggested that the e-portfolio could be used as one of strategies to elevate students’ speaking ability since it made them reflect on their speaking ability to be better through the old video collections placed on it which contain about feedback and their speaking score performance.